Recent advances and prospects for a GaN-based hybrid type ultraviolet photodetector - Zhang, Jiaxin; Deng, Liqiong; Xia, Shihong; Guo, Chenyu; Liu, Kunzi; Chen, Li; Liu, Wei; Xiao, Hui; Yang, Zhenhai; Guo, Wei; Ye, Jichun (Semiconductor science and technology, 2024)
Solid-state ultraviolet (UV) photodetectors (PDs) have received significant attention due to their advantages of small size, absence of external cooling, high selectivity and the ability to utilize the energy band structure semiconductor materials to achieve detection across various wavelengths. III-nitride thin films, as typical wide bandgap semiconductors with mature n-type and p-type doping capabilities, are ideal candidates for solid-state UV-PDs. However, a combination of III-nitride and other wide bandgap materials can either enrich the functionality of devices such as spectrum-selective and broadband UV detectionor offer opportunities to enhance device performance, including high photoresponsivity, high external quantum efficiency, low dark current and fast response time. This topical review focuses on giving a thorough review of the III-nitride-based hybrid-type UV PDs, their recent progress and future prospects. We highlight the different optical and electrical properties of various materials including GaN, Ga 2 O 3 , ZnO, perovskite, etc. By carefully choosing the materials on both sides of the heterojunction and modulating the thickness and Fermi levels and corresponding layers, p–i–n, Schottky or metal–semiconductor–metal-type PDs were successfully fabricated. They displayed outstanding device performance and novel spectral-selective properties. The advantages for future development of these hybrid-type PDs will be discussed, such as inherently formed p–n junction with large depletion regions at the interface of two different materials and capability of bandgap engineering to tune the band offset between the conduction and valence bands, thus enabling large barrier height for one type of carrier without influencing the other. The drawbacks of hybrid-type UV-PD due to poor interface quality and challenges in forming electrical contact in nanostructured hybrid UV-PD will also be discussed.